Binding abilities of a chiral calix[4]resorcinarene: a polarimetric investigation on a complex case of study - Russo, Marco; Lo Meo, Paolo (Beilstein Journal of Organic Chemistry, 2017)
Polarimetry was used to investigate the binding abilities of a chiral calix[4]resorcinarene derivative, bearing L-proline subunits, towards a set of suitably selected organic guests. The simultaneous formation of 1:1 and 2:1 host–guest inclusion complexes was observed in several cases, depending on both the charge status of the host and the structure of the guest. Thus, the use of the polarimetric method was thoroughly revisited, in order to keep into account the occurrence of multiple equilibria. Our data indicate that the stability of the host–guest complexes is affected by an interplay between Coulomb interactions, π–π interactions, desolvation effects and entropy-unfavorable conformational dynamic restraints. Polarimetry is confirmed as a very useful and versatile tool for the investigation of supramolecular interactions with chiral hosts, even in complex systems involving multiple equilibria.
Keywords: calix[4]resorcinarene; host–guest complexes; p-nitroanilines; polarimetry; supramolecular chemistry